A general iterative method for a nonexpansive semigroup in banach spaces with gauge functions - Kamonrat Nammanee (2018)
We study strong convergence of the sequence generated by implicit and explicit general iterative methods for a one-parameter nonexpansive semigroup in a reflexive Banach space which admits the duality mapping J , where is a gauge function on [ 0,∞). Our results improve and extend those announced by G. Marino and H.-K. Xu (2006) and many authors. Copyright © 2012 Kamonrat Nammanee et al.